Bio‐tillage improves soil physical properties and maize growth in a compacted Vertisol by cover crops. Issue 2 (14th February 2022) - Zhang, Zhongbin; Yan, Lei; Wang, Yuekai; Ruan, Renjie; Xiong, Peng; Peng, Xinhua
Abstract: Bio‐tillage has recently been proposed as a measure to alleviate soil compaction through biopores created by cover crop roots. The objective of this study was to determine the effect of different cover crops on soil physical properties and the succeeding maize ( Zea mays L.) growth in compacted soil. Four treatments, including no cover crop as a control (Con), alfalfa ( Medicago sativa L.), oilseed rape ( Brassica napus L.), and radish and hairy vetch mixture ( Raphanus sativus L. and Vicia villosa Roth), were carried out under both compacted and noncompacted soil conditions. Soil physical properties, such as the volumetric soil water content (SWC), bulk density, saturated hydraulic conductivity ( K s ) and air permeability at water potential of −60 hPa ( K a60 ), and maize root characteristics and yield were measured. The cover crops did not affect the soil bulk density but significantly decreased the SWC in both the compacted and noncompacted soils relative to the Con treatment. The alfalfa treatment presented significantly higher K s in the noncompacted soil and K a60 in both the compacted and noncompacted soils than the Con treatment in the soil layer depth of 20–50 cm. The three cover crop treatments improved the maize root biomass density (173.2% for 2018 and 35.6% for 2019) and root length density (50.9% for 2018 and 51.8% for 2019) relative to the Con treatment in the soil layer depth of 10–70 cm in 2018 and soil layer depth of 10–50 cm in 2019 in the compacted soil rather than in the noncompacted soil. Compared with the Con treatment, the radish mixed with hairy vetch treatment in 2018 and the oilseed rape treatment in 2019 significantly enhanced the maize yield in the compacted soil. Our results suggest that alfalfa is the best crop for improving air permeability; however, the oilseed rape and mixture of radish and hairy vetch lead to better maize growth in the compacted soil. Bio‐tillage using cover crops is effective in alleviating soil compaction. Core Ideas: Cover crops significantly reduced soil water content but did not alter bulk density. Alfalfa was the best crop for improving air permeability in compacted soil. Cover crops improved the maize root characteristics and yield in compacted soil. Oilseed rape and a mixture of radish and hairy vetch had better effects on maize growth.